Effects of motor-cognitive interaction based on dual-task gait analysis recognition in middle age to aging people with normal cognition and mild cognitive impairment - Zheng, Yuxin; Lang, Shijuan; Liang, Junjie; Jiang, Yongchun; Zhao, Biyi; Chen, Hongxin; Huang, Dongqing; Li, Qinyi; Liu, Huijin; Chen, Shudi; Yilifate, Anniwaer; Xu, Fangqiu; et al. (Frontiers in Aging Neuroscience, 2022)
Background Mild cognitive impairment (MCI) is considered a transitional stage between cognitive normality and dementia among the elderly, and its associated risk of developing Alzheimer’s disease (AD) is 10–15 times higher than that of the general population. MCI is an important threshold for the prevention and control of AD, and intervention in the MCI stage may be the most effective strategy to delay the occurrence of AD. Materials and methods In this study, 68 subjects who met the inclusion criteria were divided into an MCI group (38 subjects) and normal elderly (NE) group (30 subjects). Both groups underwent clinical function assessments (cognitive function, walking function, and activities of daily living) and dual-task three-dimensional gait analysis (walking motor task and walking calculation task). Spatial-temporal parameters were obtained and reduced by principal component analysis, and the key biomechanical indexes were selected. The dual-task cost (DTC) was calculated for intra-group (task factor) and inter-group (group factor) comparisons. Results The results of the principal component analysis showed that the cadence parameter had the highest weight in all three walking tasks. In addition, there were significant differences in the cadence both walking motor task (WMT) vs. walking task (WT) and walking calculation task (WCT) vs. WT in the MCI group. The cadence in the NE group only showed a significant difference between WMT and WT. The only differences between the MCI group and NE group was DTC cadence in WCT, and no differences were found for cadence in any of the three walking tasks. Conclusion The results show that dual tasks based on cognitive-motor gait analysis of DTCcadence in MCI have potential value for application in early identification and provide theoretical support to improve the clinical diagnosis of MCI.